A Study of Health Problems Facing During Menstruation among School Going Girls of Meerut District (International Journal of Food and Nutritional Sciences, 2022)
This paper examines the health issues school-age girls in the Meerut district face when theymenstruate. The primary goal of the research is to use factor analysis to determine and evaluatethe health factors and preventative actions that have the greatest influence during menstruation. Arandom selection of 1500 responders was made from high schools spread across several talukas inthe Meerut district. In this study, eighteen factors were taken into account. Using the SPSSsoftware, factor analysis was used to identify the most important health and precautionary aspects.